Processes of manufacture of plastics products - Carrión Nin, José (2000)
This article shows the process of molding plastic extrusion and injection information that will provide a comprehensive and simple idea in this type of industrial activity.Extrusion is a process used to manufacture products such as PVC pipes , rods and the insulated wire coating plastics and other products of constant section. This process involves heating the plastic and cause its output by pressure through a hole in a certain way and then cooling it in a machine called an extruder.The injection is performed by the injection molding machines in a similar way to the extruders ; except that the extruder while continuously preiona plastic material through unamatriz , makes a fuel entering a cold mold . Then wait until the cold molded material is to be removed from the mold before it is refilled . is used to manufacture products such as taznes , mugs , toys, etc.